(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: This research examines the legal basis on which the administration relies when directing administrative activity through oral orders. Such orders represent a manifestation of administrative authority within the state apparatus and reflect the legal relationship between superiors and subordinates. Objective: The research aims to clarify the legal basis for the legitimacy of complying with oral administrative orders and to determine the legal responsibility arising from compliance with an unlawful oral administrative order. Methodology: The research adopts a comparative analytical approach based on the examination of legal scholarship and statutory provisions, with reference to the French, Egyptian, and Iraqi legal systems. Results: The findings indicate that oral administrative orders do not constitute a departure from the principle of legality; rather, they represent a form through which the administration expresses its will in an unwritten manner. Employees who fail to comply with such orders may incur legal or disciplinary liability. Conclusion: Oral administrative orders constitute one of the administrative mechanisms used in managing public services. Issued by an administrative superior within the scope of his authority, they are binding on subordinate employees by virtue of the duty of obedience. Where such orders affect the legal status of individuals or employees, they may acquire the character of administrative decisions subject to annulment proceedings; otherwise, they remain internal directives governing the operation of the public service.